MENA Quarterly Economic Brief : Plunging Oil Prices - Lili Mottaghi (World Bank, Washington, DC, 2015)
In the three months since most observers, including the World Bank, issued their last forecasts, the Middle East and North Africa (MENA) Region has changed substantially. Political tensions have eased somewhat with presidential and legislative elections completed in a few countries. This issue of the MENA Quarterly Economic Brief focused on the implications of low oil prices for eight developing countries, the MENA-8 (oil importers: Egypt, Tunisia, Lebanon and Jordan and oil exporters: Iran, Iraq, Yemen and Libya) and the economies of the GCC (Gulf Cooperation Council), who play a major role in providing funds in the form of aid, investment, tourism revenues and remittances to the rest of the countries of the region. Several assumptions are also made about future oil prices taking into account several variables. All projections are based on statistical information available through early January 2015.